Heat inactivation of stable proteinaceous particles for future sample return mission architecture - Seto, Emily P.; Hirsch, Aspen L.; Schubert, Wayne W.; Chandramowlishwaran, Pavithra; Chernoff, Yury O. (Frontiers in Microbiology, 2022)
The National Aeronautics and Space Administration (NASA) and the European Space Agency (ESA) are studying how to improve the safety of future planetary science sample return missions that would bring back materials to Earth . Backward planetary protection requirements have been identified as a critical technology development focus in order to reduce the possibility of harm to Earth’s biosphere from such returned materials. In order to meet these challenges, NASA has identified the need for an appropriate suite of biological indicators (BIs) that would be used to develop, test, and ultimately validate sample return mission sterilization systems. Traditional BIs are defined as a test system composed of viable microorganisms that are inactivated when necessary conditions are met during sterilization procedures, providing a level of confidence in the process. BIs used traditionally at NASA have been driven by past mission requirements, mainly focused on spore-formers. However, spore-based BIs are insufficient as the only analog for a nominal case in sample return missions. NASA has directed sample return missions from habitable worlds to manage “potential extraterrestrial life and bioactive molecules” which requires investigation of a range of potential BIs. Thus, it is important to develop a mitigation strategy that addresses various known forms of biology: from complex organisms to biomolecular assemblies (including self-perpetuating non-nucleic acid containing structures). The current effort seeks to establish a BI that would address a stable biomolecule capable of replication. Additional engineering areas that may benefit from this information include applications of brazing, sealing, and impact heating, and atmospheric entry heating. Yeast aggregating proteins exhibit aggregation behavior similar to mammalian prion protein and have been successfully employed by researchers to understand fundamental prion properties such as aggregation and self-propagation. Despite also being termed “prions”, yeast proteins are not hazardous to humans and can be used as a cost effective and safer alternative to mammalian prions. We have shown that inactivation by dry heat is feasible for the prion formed by the yeast Sup35NM protein, although at higher temperature than for bacterial spores.